Usability Assessment for Classroom-Based Mobile Application to Enhance Communication - Nik Ahmad, Nik Azlina; Zahri, Noorul Amilin (Journal of Computing Technologies and Creative Content, 2020)
This paper presents a research about usability testing for a mobile application named CoMAC: A Communication Mobile Application for Classroom. CoMAC is an application that developed for the usage of pre-school to handle the administrative task and monitor child’s assessment. This research paper focus on the usability testing part where the evaluation method is based on the quantitative methodology conducted on people who has a teaching and parenting background. This testing is important because it could help the researcher to identify the level of performance of the application and level of satisfaction of the user. The results of the testing show that the application evaluated is suitable for pre-school and have some room that can be improved.